Discrete-event system simulation - Banks, Jerry; Carson, John.; Nelson, Barry L.; Nicol, David ([S.l.] : Prentice Hall, 2004)
This book provides a basic treatment of discrete-event simulation, including the proper collection and analysis of data, the use of analytic techniques, verification and validation of models, and designing simulation experiments. Contains up-to-date treatment of simulation of manufacturing and material handling systems. Includes numerous solved examples. Offers an integrated website. Explains how to interpret simulation software output. For those interested in learning more about discrete-event simulation.